Efforts to Improve Green Performance Through Green Human Resource Management Companies in Batam - Evi Silvana Muchsinati; Tan Le Xuan (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to investigate how to improve Developing Green Abilities, Motivating Green Initiatives, Providing Green Opportunities, Green Process Inovation through Green Human Resource Management. Many companies still focus on increasing profits by maximizing the production process, without paying attention to the impact on the surrounding environment. Based on data for the 2022 period, there is still a lot of hazardous and toxic waste in Batam City, which can cause environmental damage and be dangerous for the health of the people of Batam City. In this research, researchers surveyed via questionnaire as a technique for collecting primary data. Questionnaires were distributed to employees of PT. Phillips, PT. Panasonic, PT. TDK Electronics Indonesia in Batam City because these three companies produce and sell electronic goods, where there is still a lot of electronic waste which is classified as dangerous (Pratiwi et al, 2016). The questionnaire was distributed to 250 respondents using the SPSS application to test the hypothesis. The research results showed that of the 10 hypotheses tested, 7 hypotheses had an effect on each other and the other 3 hypotheses had no effect.